A arte na elaboração de sequências didáticas para aulas de história de alunos dos anos finais de ensino fundamental na perspectiva da educação para as relações étnico-raciais - Melo, Susy Cléa Lisbôa (2020)
The present study aimed to propose didactic sequences for the History teaching that can contribute to the education of ethnic-racial relations in Middle School classes, respecting what the Law 10.639 / 2003 and Law 11.645 / 2008 say that amended Law 9.394 of December 20, 1996, which determines the compulsory of Indigenous and Afro-Brazilian Culture and History teaching in public and private institutions of education in the country. In this analysis we privilege the pertinent reflections to Law nº 10.639 / 2003, considering that our focus is on the work‟s fulfillment targeted the valorization of black culture and mainly for realizing that in the readings made, the authors still emphasize that Law in their productions, mainly because this is the first legislation to deal with the obligation of teaching that values the black / african ancestry in the construction of identities. In this sense, we proposed ourselves to understand teaching for ethnic-racial relations as a fundamental instrument to the formation of identity and the exercise of democracy, through the use of art in history classes on the final years of Middle School. Therefore, we aimto develop didactic sequences that include resources of valorization to the black culture and combating racism; as well suggesting the use of these didactic sequences to build historical knowledge. Our interest in the topic has emerged since graduation in History, due to the absence of disciplines that favored this teaching about African and Afro-Brazilian culture. The Professional Master‟s degree in History Teaching sharpened this need to develop a differentiated and targeted work to the sociocultural scope, emphasizing the need of ethnic-racial education in the construction of identities, using the most diverse sources of knowledge accessible to the student, beyond what the textbook offers in the construction of historical knowledge. In this context, we use concepts that promote and legitimize ethnic-racial education as primordial element in the exercise of democracy. With regard to the pedagogical practices in the History Teaching and the use of didactic sequences as resources that dynamize this construction of historical knowledge, we based on theories that ratify the importance of them (sequences) as an instrument that allows the accomplishment of targeted and differentiated activities. This work was developed in a qualitative approach and consisted of the elaboration of pedagogical material for use in classroom in a perspective of continuity and resignification of historical knowledge. It is expected that the activities can be applied and adapted to the reality of each school and that they show how black culture makes up our identities and how we can use this recognition to combat racism.